Layanan Bimbingan Konseling Menggunakan Teknik Focus Group Discussion (FGD) Untuk Mengatasi Konflik Organisasi Intra Kampus Di UKMK UIN Raden Fatah Palembang - Nandoe, Nandoe; Suryati, Suryati; Noviza, Neni (CV. ITTC INDONESIA, 2023)
A dynamic interpersonal procedure with a focus on conscious thought and behavior is group therapy. Methods include expressing ideas and emotions openly that are grounded in truth, being transparent about one's intense emotions, and cultivating mutual trust, care, understanding, and support. This study aims to determine the differences in the vision and mission adopted by each intra-campus organizational unit, to find out how the Focus Group Discussion (FGD) approach is used for counseling advice to address intra-campus organizational problems. This study uses a qualitative method of field research. Study participants included UKMK LPTQ&D and UKMK LDK. using interviews, observation, and documentation as data collection methods. data analysis techniques which include data reduction, data visualization, and drawing conclusions According to the study of the problems faced by intra-campus groups, including incompatibility of goals and missions. The problems experienced are that they bring down UKMK organizations to each other, feel the most righteous, take sympathy from each other by badmouthing other UKMK, feel most right with the application of religious learning. In the process of implementing group counseling guidance using the Focus Group Discussion (FGD) technique there are 3 stages including: 1). Preparation Stage (appropriate equipment and media are needed in the discussion) 2). Opening (Start explaining the meeting procedures, start the meeting by asking broad questions that are not related to the issue or topic of discussion, then after the process is complete then ask leading questions by using the reference guide. 3). Conclusion (delivering the results of the discussion, if there are corrections or additions to the findings, say it once again, thank you, and convey it will be used as a guide for future planning. Using the Focus Group Discussion (FGD) technique There is unity between the two UKMK LPTQ & D and UKMK LDK so that there is no longer any difference.